Por uma sustentabilidade patrimonial: os usos de medidas de compensação na política pública de proteção do patrimônio cultural de Belo Horizonte - Gilvan Rodrigues dos Santos (2022)
This dissertation seeks to investigate the use of compensation measures in understanding the current processes of preservation of cultural assets and the consequences of the use of these instruments along with the heritage preservation policy carried out in the city of Belo Horizonte, Minas Gerais, Brazil. The objective is to explore theoretically and methodologically the aspects of compensation measures, especially in the history of formulating their concept, in the elaboration of legal frameworks and, still, in the practical use by Organs competent bodies of the Municipality of Belo Horizonte. For that, it uses the deductive and dialectical method, through the historical procedure, which is based on the crossing of bibliographic research, documental and field survey and, finally, synthesis work. The investigation is based on two phases: the first on the analysis of guidelines and regulations; the second in the analysis of the applicability of the compensation measures in the existing cultural heritage, through the mapping of use on the cultural heritage listed. In this sense, we seek to know the scope of compensation measures as an instrument for managing the urban cultural heritage listed in Belo Horizonte.